Respuesta :

Answer:

B. [tex]g(x)=5(x-4)[/tex]

Step-by-step explanation:

we are given

[tex]f(x)=5x[/tex]

It is shifted right side by 4 units

We know that

Whenever any function is shifted right side by 'a' units

we can replace x as x-a

x----->(x-a)

Here , it is shifted right side by 4 units

so, we can replace x as x-4

we get

[tex]g(x)=f(x-4)[/tex]

[tex]g(x)=5(x-4)[/tex]

Answer: B. [tex]g(x)=5(x-4)[/tex]

Step-by-step explanation:

When we shift a function h(x) by n units right , the new function  will be :-

[tex]d(x)=h(x-n)[/tex]

Given : There is a horizontal shift of [tex]f(x)=5x[/tex] by 4 units to the right, then new function  will be :-

[tex]g(x)=f(x-4)\\\\\Rightarrow\ g(x)=5(x-4)[/tex]

Hence, the function represents a horizontal shift of ƒ(x) = 5x by 4 units to the right is [tex]g(x)=5(x-4)[/tex]